PERITONEAL ADHESIONS TYPE I, III AND TOTAL COLLAGEN ON POLYPROPYLENE AND COATED POLYPROPYLENE MESHES: EXPERIMENTAL STUDY IN RATS - ROSSI,Lucas Félix (2017)
ABSTRACT Background: Hernia correction is a routinely performed treatment in surgical practice. The improvement of the operative technique and available materials certainly has been a great benefit to the quality of surgical results. The insertion of prostheses for hernia correction is well-founded in the literature, and has become the standard of treatment when this type of disease is discussed. Aim: To evaluate two available prostheses: the polypropylene and polypropylene coated ones in an experimental model. Methods: Seven prostheses of each kind were inserted into Wistar rats (Ratus norvegicus albinus) in the anterior abdominal wall of the animal in direct contact with the viscera. After 90 days follow-up were analyzed the intra-abdominal adhesions, and also performed immunohistochemical evaluation and videomorphometry of the total, type I and type III collagen. Histological analysis was also performed with hematoxylin-eosin to evaluate cell types present in each mesh. Results: At 90 days the adhesions were not different among the groups (p=0.335). Total collagen likewise was not statistically different (p=0.810). Statistically there was more type III collagen in the coated polypropylene group (p=0.039) while type I was not different among the prostheses (p=0.050). The lymphocytes were statistically more present in the polypropylene group (p=0.041). Conclusion: The coated prosthesis was not different from the polypropylene one regarding the adhesion. Total and type I collagen were not different among the groups, while type III collagen was more present on the coated mesh. There was a greater number of lymphocytes on the polypropylene mesh.